PENGARUH PERMAINAN BOX PUPPET TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI RA AL-MUNAWWARAH DESA TAGARAJA KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Vebriana, Esah; Novianti, Ria; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Based on the results of observations in the field can be seen that the ability to recognize the concept of the number of children aged 4-5 years has not developed optimally. So it needs to use the box peppet game. This study aims to determine the effect of box puppet game towerd number concept ability of children 4-5 year in RA Al-Munawwarah Desa Tagaraja Kecamatan Kateman Kabupaten Indragiri Hilir. The study used experimental methods with the design of one group pre-test post-test design. The samples used in this study were 15 students. The data collection technique used are observation. The data analysis technique used the t-test using the SPSS 20 program. The research hypothesis was that there was influence of the effect of box puppet game towerd number concept ability of children 4-5 year in RA Al-Munawwarah Desa Tagaraja Kecamatan Kateman Kabupaten Indragiri Hilir. Based on data analysis it is known that tcalculated = 13,315 > ttable = 2,145 with Sig. (2-tailed) = 0.000. Because Sig < 0,05 it can be concluded that there are difference in the ability to recognize the concept of numbers before and after the box peppet game. It can be interpreted that there is the influence of the effect of box puppet game towerd number concept ability of children 4-5 year in RA Al-Munawwarah Desa Tagaraja Kecamatan Kateman Kabupaten Indragiri Hilir which is significant at 57,22%.Keyword: Concept Of Numbers, Box Peppet